Yield of Clinical Screening for Hypertrophic Cardiomyopathy in Child First-Degree Relatives: Evidence for a Change in Paradigm. Issue 3 (16th July 2019) - Norrish, Gabrielle; Jager, Joanna; Field, Ella; Quinn, Ellie; Fell, Hannah; Lord, Emma; Cicerchia, Marcos N.; Ochoa, Juan Pablo; Cervi, Elena; Elliott, Perry M.; Kaski, Juan Pablo
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is a heritable myocardial disease with age-related penetrance. Current guidelines recommend clinical screening of relatives beginning at 10 years of age, but the clinical value of this approach has not been systematically evaluated. Methods: Anonymized clinical data were collected from children referred for family screening between 1994 and 2017 after diagnosis of HCM in a first-degree relative. Results: Of 1198 consecutive children (⩽18 years of age) from 594 families who underwent serial evaluation (median, 3.5 years; interquartile range, 1.2–7), 32 individuals met diagnostic criteria at baseline (median maximal left ventricular wall thickness, 13 mm; interquartile range, 8-21 mm), and 25 additional patients developed HCM during follow-up. Median age at diagnosis was 10 years (interquartile range, 4–13 years); 44 (72%) were ⩽12 years of age. Median age of affected patients at the last follow-up was 14 years (interquartile range, 9.5–18.2 years). A family history of childhood HCM was more common in those patients diagnosed with HCM (n=32 [56%] versus n=257 [23%]; P <0.001). Eighteen patients (32%) were started on medication for symptoms; 2 (4%) underwent a septal myectomy; 14 (25%) received an implantable cardioverter-defibrillator; 1 underwent cardiac transplantation; 2 had a resuscitated cardiac arrest; and 1 died after a cerebrovascular accident. Conclusions: Almost 5% of first-degree child relatives undergoing screening meet diagnostic criteria for HCM at first or subsequent evaluations, with the majority presenting as preadolescents; a diagnosis in a child first-degree relative is made in 8% of families screened. The phenotype of familial HCM in childhood is varied and includes severe disease, suggesting that clinical screening should begin at a younger age. Abstract : Supplemental Digital Content is available in the text.